European influence in ITU‐R: the end of an era of dominance?. Issue 4 (2014) - Mohamed Ali El‐Moghazi; Jason Whalley; James Irvine
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to examine the influence of the European countries in Region 1 of the Radio Sector of the International Telecommunications Union (ITU‐R). More specifically, the focus is on the World Radiocommunication Conference 2012 meeting to explore whether European influence is in decline. Design/methodology/approach – This article adopts in‐depth case study of the 700‐MHz issue. Qualitative data are drawn from semi‐structured interviews with key stakeholders who participated at the World Radiocommunication Conference 2012 meeting. Findings – This article concludes that the influence of European countries in the ITU‐R in Region 1 has changed. The influence of Arab and African countries has increased, with that of European countries declining. However, European countries remain more influential than their African and Arab counterparts. Research limitations/implications – This article sheds light on an often overlooked but pivotal element of the international spectrum allocation mechanism. Originality/value – This article sheds light on important developments in the international spectrum policy that are largely overlooked in the current debate.